Modelling Of Power Converter Wpt System Based On Inductor Current Ripple - Amirul Shafiq, Khairuddin (2021)
Buck power converter is one of the power converters that can be seen in our life nowadays. A buck converter (step-down converter) is a DC-to-DC power converter that steps down voltage from its input supply to its output while drawing less average current. Switching frequencies in buck converter design help in reducing the size of inductor and decrease inductor current ripple. However, it can cause the power loses and decrease efficiency due to inductor core losses. This project presents the simulation of method of harness the switching ripple energy from the inductor by using Wireless Power Transfer (WPT) to compensate the inductor core losses. By using buck converter system as model, 2-coil and 4-coil WPT system need to be replace with the inductor in the buck converter. The data were collected by manipulated parameter of the buck converter such as frequency, duty cycle and coupling factor. The switching frequency of the buck converter need to be in the suitable frequency in order to Buck-WPT to be operate. To obtain higher output voltage in the Buck-WPT converter, duty cycle and coupling factor need to be in certain value. The Buck-WPT circuit is simulate using the Simulink/MATLAB with a suitable tool for the circuit. This project concludes by studies the effect of buck converter parameter toward 2-coil and 4-coil Buck-WPT converter.